2020
DOI: 10.1002/jia2.25620
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the ECHO trial results: modelling the potential impact of changing contraceptive method mix on HIV and reproductive health in South Africa

Abstract: Introduction: Some observational data suggest that the progestogen injectable contraceptive depot medroxyprogesterone acetate (DMPA) may increase a woman's risk of HIV acquisition but a randomized clinical trial did not find a statistically significant increase in HIV risk for women using DMPA compared to two other methods. However, it could not rule out up to 30% increased HIV risk for DMPA users. We evaluate changes to contraceptive method mix in South Africa under different assumptions about the existence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The inconsistent findings of the effect of progestin-only contraceptives on the vaginal microbiota within and/or between sub-populations may be explained by host genetics and gene polymorphisms ( Dabee et al., 2021 ), however further research is needed. The effect of DMPA on the vaginal microbiota is of particular interest due to its high rate of use in sub-Saharan Africa, and concerns it may enhance HIV transmission/acquisition ( Galvin and Cohen, 2004 ; Curtis et al., 2020 ; Smith et al., 2020 ). This was reflected in our study screening process, which identified most progestin-only studies investigated the impact of DMPA on the vaginal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent findings of the effect of progestin-only contraceptives on the vaginal microbiota within and/or between sub-populations may be explained by host genetics and gene polymorphisms ( Dabee et al., 2021 ), however further research is needed. The effect of DMPA on the vaginal microbiota is of particular interest due to its high rate of use in sub-Saharan Africa, and concerns it may enhance HIV transmission/acquisition ( Galvin and Cohen, 2004 ; Curtis et al., 2020 ; Smith et al., 2020 ). This was reflected in our study screening process, which identified most progestin-only studies investigated the impact of DMPA on the vaginal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This change, according to the key informants of this study resulted in decreased numbers of nurses who are specialised in contraceptive carewhich has been overshadowed by the impact of HIV/AIDS on the health care system [29,63]. There is a need for PHC nurses to be well trained and informed about the available contraceptive methods, their mechanism of action, potential side-effects, and interactions with other treatment regimes especially given the concerns around DMPA, increased risk for HIV acquisition, and method switching [64,65]. Insufficient training of HCPs was reported as one of the reasons for frequent discontinuation and rumours about side effects of the Implant [60].…”
Section: Structure Related Componentsmentioning
confidence: 99%